The role of Corporate Social Investment (CSI) programmes on developing small and medium enterprises (SMEs): The case of Sappi Southern Africa in the local communities of Umkomaas in the South Coast of KwaZulu Natal - Ntuli, Zandile Phindile (University of the Witwatersrand, Johannesburg, 2024)
Africa. The government has called on corporations to help transform the country through Corporate Social Investment (CSI) to accelerate socioeconomic development. This study focused on CSI as part of a broader corporate social responsibility (CSR) framework. South Africa has seen significant growth in CSI, due in part to the implementation of the Black Economic Empowerment (BEE) Code of Good Practice, which requires businesses to contribute to the country's reconstruction efforts. As a result, many businesses have adopted social development strategies as part of their core business objectives. The small and medium enterprises (SMEs) economy is considered crucial to achieving some of the objectives for post- apartheid reconstruction and development, such as economic restructuring and alleviation of poverty. Given the slow growth of new job opportunities in large corporations, the developmental support of SMEs is viewed as a vital vehicle for generating employment. Using a qualitative approach, the study explored the role of CSI programmes in developing SMEs, with a focus on Sappi Southern Africa’s Saiccor mill in Umkomaas on the South Coast of KwaZulu Natal (KZN). A case study design was adopted to obtain in-depth information from participants concerning Sappi's CSI programmes. A semi-structured interview schedules was used as a research instrument, with one-on-one individual interviews used as a method of data collection. The study consisted of 12 purposively sampled participants. The findings revealed that the local community of Umkomaas benefited from the CSI programmes. The CSI programmes contributed positively to the development of local SMEs. In addition, the unemployed youth gained skills through the various skills development initiatives to become economically active. To tackle poverty, unemployment and inequality in South Africa, a renewed commitment from the various economic sectors is needed, notably the private sector with the influence and resources.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, Wits School of Art, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Corporate social investment; corporate social responsibility; community; small and medium enterprises; social impact; Umkomaas- KwaZulu Natal; SDG-8: Decent work and economic growth